The Impact of the Development of the Digital Hijrah Trend in Building Muslim Millennial Communities on Social Media Platforms - maulana, Ade Hilman (Jurnal Ar Ro'is Mandalika (Armada), 2024)
The rapid growth of digital platforms has significantly influenced various aspects of society, including religious practices and community building. This study explores the impact of the digital hijrah trend in the construction of Muslim millennial communities on social media platforms. Using a qualitative approach, this research employs a literature study and library research method to analyze existing literature, articles, and online content related to the hijrah trend. The study examines how the digital hijrah movement, which emphasizes spiritual transformation and religious commitment, resonates within the millennial generation and fosters a sense of community. The findings indicate that the hijrah trend on social media serves as a platform for Muslims to share personal stories, religious knowledge, and support one another in their faith journey. Additionally, the digital hijrah community creates a virtual space for engagement, interaction, and the formation of shared values among Muslims, especially the millennial demographic. This study contributes to understanding the role of social media in shaping religious communities and offers insights into how digital platforms can foster positive social and religious transformation within contemporary Muslim societies. The findings also highlight the potential of digital media in enhancing religious identity and community solidarity in the digital age.